Low bit Rate Video Quality Analysis Using NRDPF-VQA Algorithm - Subrahmanyam CH; Venkata Rao D; Usha Rani N (Institute of Advanced Engineering and Science, 2015)
In this work, we propose NRDPF-VQA (No Reference Distortion Patch Features Video Quality Assessment) model aims to use to measure the video quality assessment for H.264/AVC (Advanced Video Coding). The proposed method takes advantage of the contrast changes in the video quality by luminance changes. The proposed quality metric was tested by using LIVE video database. The experimental results show that the new index performance compared with the other NR-VQA models that require training on LIVE video databases, CSIQ video database, and VQEG HDTV video database. The values are compared with human score index analysis of DMOS.